ECO LABEL SYSTEM DEVELOPMENT EVOLUTION - G‘ulomov Xayotbek Xasanboy o’g‘li (Web of Journals Publishing, 2024)
Through this article, we can see the rapid evolution of the Ecolabel and its licensing stages. Classification of eco-labels is also indicated in the article. Also, statistical data on obtaining a license by country and by product mark were analyzed.
Keywords: Green Stickers, Ecolabel, Evolution, Licences, Distribution, ISO 14000, per country.